Fermented beverages among indigenous Latin American societies - Lasso García, Christian (2024)
Purpose: Traditional fermented beverages are a valuable cultural, economic, and social heritage of Latin American societies that deserve to be preserved and strengthened with sustainable development and respect for diversity. Therefore, this article will demonstrate, through scientific literature, the importance for indigenous societies and the nutritional contributions of the most traditional beverages of North and South America. Methods: This systematic review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) verification protocol. The study focused on exploring the nutritional information of South and Central American fermented beverages. The search was conducted in the Biomed, PubMed, ScienceDirect, Scopus, Scielo, and Google Scholar databases to identify publications published within the past 15  years. Results: However, the presence of toxic compounds such as biogenic amines and phenols that affect the quality of the product and human health has been detected. In addition, it was found that macro-and micronutrients, vitamins, and microorganisms differ according to the type of raw material used. It was concluded that corn is the most widely used raw material to produce fermented beverages in Latin America. At the same time, Mexico has conducted more research on this product, and most analyses are being carried out on the use of corn in the production of fermented beverages. In addition, several studies have shown that using validated and standardized methodologies to detect biogenic weapons is crucial to ensure accurate identification, effective response, and compliance with legal and security requirements in this critical area.